2015
DOI: 10.1051/fruits/2015023
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of fruit quality by moderate water deficit in three plum cultivars (Prunus salicinaL.) cultivated in a semi-arid region

Abstract: Introduction. Drought can affect the qualitative and nutritional attributes of plum (Prunus salicina L.). The aim of this work was to study the effect of regulated deficit irrigation (RDI) on the quality of plum fruits. Materials and methods. Experiments were conducted during two consecutive seasons (2011-2012) with three cultivars ('Black Diamond', 'Black Gold' and 'Black Star') recently introduced in the region of Regueb (center of Tunisia) characterized by a semi-arid climate. During the fruit growth period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 29 publications
(36 reference statements)
3
20
0
Order By: Relevance
“…Different cultivars of strawberry (Bordonaba & Terry, 2010;Terry, Chope, & Bordonaba, 2007) (Miller,Smith,Boldingh,&Johansson,1998).Theimpact of deficient irrigation on sucrose content in fruits of nectarine, peach, plum, satsuma mandarins, mango fruit and strawberry were also investigated. Elevations in sucrose content in fruits of nectarine (Thakur & Singh, 2012), plum (Maatallah et al, 2015), and satsuma mandarins (Yakushiji et al, 1998) were detected under deficient irrigation, while no impact of such condition on the sucrose content in mango fruit and strawberry (Bordonaba & Terry, 2010;Terryetal.,2007)werefound.Inpeach,thecontentofsucrose decreased in response to increased water deficit (Rahmati etal.,2018).Theplantsgrowingwildlywillneverbeirrigated,but precipitation contributes in the same way as irrigation to the plant growth.Inourinvestigationsconductedonblackcurrants (Zheng, Yangetal.,2009),theplantswerewildlygrowninopenfieldsand the precipitation levels were recorded for the correlation studies between precipitation and the contents of sugars in ripe berries.…”
Section: Althoughitisspeculatedthatwaterdeficitshouldhaveinhib-mentioning
confidence: 92%
See 1 more Smart Citation
“…Different cultivars of strawberry (Bordonaba & Terry, 2010;Terry, Chope, & Bordonaba, 2007) (Miller,Smith,Boldingh,&Johansson,1998).Theimpact of deficient irrigation on sucrose content in fruits of nectarine, peach, plum, satsuma mandarins, mango fruit and strawberry were also investigated. Elevations in sucrose content in fruits of nectarine (Thakur & Singh, 2012), plum (Maatallah et al, 2015), and satsuma mandarins (Yakushiji et al, 1998) were detected under deficient irrigation, while no impact of such condition on the sucrose content in mango fruit and strawberry (Bordonaba & Terry, 2010;Terryetal.,2007)werefound.Inpeach,thecontentofsucrose decreased in response to increased water deficit (Rahmati etal.,2018).Theplantsgrowingwildlywillneverbeirrigated,but precipitation contributes in the same way as irrigation to the plant growth.Inourinvestigationsconductedonblackcurrants (Zheng, Yangetal.,2009),theplantswerewildlygrowninopenfieldsand the precipitation levels were recorded for the correlation studies between precipitation and the contents of sugars in ripe berries.…”
Section: Althoughitisspeculatedthatwaterdeficitshouldhaveinhib-mentioning
confidence: 92%
“…The impact of deficient irrigation on sucrose content in fruits of nectarine, peach, plum, satsuma mandarins, mango fruit, and strawberry were also investigated. Elevations in sucrose content in fruits of nectarine (Thakur & Singh, ), plum (Maatallah et al, ), and satsuma mandarins (Yakushiji et al, ) were detected under deficient irrigation, while no impact of such condition on the sucrose content in mango fruit and strawberry (Bordonaba & Terry, ; Terry et al, ) were found. In peach, the content of sucrose decreased in response to increased water deficit (Rahmati et al, ).…”
Section: Sugarsmentioning
confidence: 99%
“…Deficit irrigation (DI) is a sustainable way to use the water resources in the Mediterranean cropping systems. Results from the scientific literature on DI allow concluding that it is possible to reduce irrigation volumes without penalizing yields ( Fereres and Soriano, 2007 ; Ruiz-Sánchez et al., 2010 ; Ripoll et al., 2014 ; Maatallah et al., 2015 ). In addition, in the case of tree cultivation systems, two additional advantages can be achieved through DI: improvement of fruit quality in terms of higher SSC (soluble solid content) and control of tree vigor ( Crisosto et al., 1994 ; Behboudian and Mills, 1997 ; Mpelasoka et al., 2000 ; Faci et al., 2014 ; Guizani et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…These changes in chemical properties and biochemical composition of fruit induced by RDI have been reported previously in similar studies [51,57] but with quantitative differences due to different experimental conditions, RDI intensities and cultivars. Increased SSC in plum was found to be largely due to an enhancement of sucrose accumulation in the fruit and not because glucose and fructose concentrations decreased under RDI [26] . The higher accumulation of sucrose in fruit under RDI is likely related to an increase in starch hydrolysis and carbohydrate translocation from vegetative organs to the fruit under water stress conditions [58] .…”
Section: Chemical and Biochemical Quality Indicesmentioning
confidence: 82%
“…RDI applied to peach during the late stages of fruit growth significantly increased the ratio of SSC to titratable acidity with a more reddish coloration of the fruit skin, representing a large improvement in fruit quality [24,25] . Water stress in plum imposed through RDI during the fruit growth period induced an improvement in fruit quality with increasing soluble solid, soluble sugar, phenolic compound and flavonoid contents associated with a decrease in total acidity [26] . Water stress imposed in almond through RDI substantially maintained kernel nutrition quality, especially regarding lipid and tocopherol contents [27] .…”
Section: Introductionmentioning
confidence: 99%